2018
DOI: 10.2478/jlecol-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Extinction of Agricultural Land in the Sudetes - A Case Study in the Landscape of Highlands and Mountains

Abstract: The Sudetenland has undergone a dramatic development in Czechia. Above all, the frontier regions of the then Czechoslovakia lost due to the decision on the displacement of the Sudeten Germans in 1945 almost 3 million native inhabitants, who left their settlement areas in several waves by 1947. This change affected up to 3 million hectares of agricultural land that became the state property. This had in many places eliminated the traditional way of farming and the disruption of ownership relations consequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…1), forest ownership patterns and thereby ownership continuity underwent large changes caused by collectivization in those European countries with socialist governments [75,[87][88][89]. Furthermore, expropriation after the Second World War resulted in widespread nationalization of forests and natural oldfield succession on abandoned former private farmland [63,90,91]. In particular, centralized and intensified forestry in socialist countries caused homogenization of both stand structures and tree species composition, the latter with an emphasis on conifers [87][88][89].…”
Section: Countries With Socialist Governmentsmentioning
confidence: 99%
“…1), forest ownership patterns and thereby ownership continuity underwent large changes caused by collectivization in those European countries with socialist governments [75,[87][88][89]. Furthermore, expropriation after the Second World War resulted in widespread nationalization of forests and natural oldfield succession on abandoned former private farmland [63,90,91]. In particular, centralized and intensified forestry in socialist countries caused homogenization of both stand structures and tree species composition, the latter with an emphasis on conifers [87][88][89].…”
Section: Countries With Socialist Governmentsmentioning
confidence: 99%
“…As this study focuses on agricultural land, vectorisation was not performed in the entire studied territory, but only in areas with agricultural land present in 2018 or 1953. Similar approaches were taken in other studies such as Forejt et al 39 , Demková and Lipský 38 , and Zelinka 33 . A spatiotemporal analysis of changes was performed in ArcGIS 10.6 using the overlay analysis tool Itersect 34 .…”
Section: Methodsmentioning
confidence: 79%
“…This research builds on the results of a study conducted in rural areas of higher altitudes in 2017 33 . The comparative study carried out in 2017 at higher altitudes of Czechia indicated large differences in the overgrowth of agricultural land by forests in the depopulated areas and in the areas that remained settled.…”
Section: Introductionmentioning
confidence: 99%